Interleukin-10 but not Transforming Growth Factor beta inhibits murine activated macrophages Paracoccidioides brasiliensis killing: Effect on H2O2 and NO production - Moreira, Ana Paula [UNESP]; Dias-Melicio, Luciane Alarcao [UNESP]; Victoriano Campos Soares, Angela Maria [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
Paracoccidioidomycosis is caused by the thermally dimorphic fungus Paracoccidioides brasiliensis (P brasiliensis). Most often, this mycosis runs as a chronic progressive course affecting preferentially the lungs. In vitro fungicidal activity against a high virulent strain of P brasiliensis by murine peritoneal macrophages preactivated with IFN-gamma or TNF-alpha is high and correlates with increased NO and H2O2 production. Within this context, the purpose of this work was to study the role of suppressor cytokines, such as IL-10 and TGF-beta, in this process. Incubation of either IFN-gamma or TNF-alpha with IL-10 inhibits fungicidal activity of these cells However, TGF-beta had no effect on fungicidal activity of IFN-gamma or TNF-alpha-activated macrophages. The suppression of fungicidal activity by IL-10 correlated with the inhibition of NO and H2O2 production supporting the involvement of these metabolites in P brasiliensis killing These results suggest that IL-10 production in vivo could represent an evasion mechanism of the fungus to avoid host immune response (C) 2010 Elsevier Inc All rights reserved.
Keywords: Murine paracoccidioidomycosis; Macrophages; Fungicidal activity; IL-10; TGF-beta; NO; H2O2